Effects of Using Thermocomposted Frass from Black Soldier Fly Larvae as a Germination Substrate on the Phytotoxicity, Germination Index, Growth and Antioxidant Contents in Kale (Brassica oleracea) - Hugo González-Lara; Benito Parra-Pacheco; Humberto Aguirre-Becerra; Ana A. Feregrino-Perez; Juan Fernando Garcia-Trejo (Agronomy, 2024)
Frass generated during the production of black soldier fly larvae is attracting the interest of scientists and horticultural producers because it is a material made from the biotransformation of organic waste, it contains several nutrients that can be used by plants, and it has a biostimulant capacity that has become a recent focus. Thermal composting is a stabilization process that improves the physical and chemical properties of treated wastes, allowing better performance in plants compared to the waste in its fresh state. In this research, thermocomposted frass was evaluated as a germination substrate for kale seeds (Brassica oleracea). To achieve this, the phytotoxicity of increasing concentrations of frass was evaluated by examining the germination of kale seeds, and seedlings were grown for 30 days in germination substrates mixed with 20, 40, 60, 80, and 100% frass under greenhouse conditions. The treatment with 20% frass showed the highest values of seedling height, stem diameter, number of leaves, length and width of the first true leaf and length and width of cotyledons, and reduced the contents of phenols, tannins and antioxidants. However, the content of flavonoids increased compared to the control and the rest of the mixtures.